2020
DOI: 10.1111/geb.13121
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diversity of North American ant communities: Cold tolerance but not heat tolerance tracks ecosystem temperature

Abstract: Aim: In ectotherms, gradients of environmental temperature can regulate metabolism, development and ultimately fitness. The thermal adaptation hypothesis assumes that thermoregulation is costly and predicts that more thermally variable environments favour organisms with wider thermal ranges and thermal limits (i.e., critical thermal minima and maxima, CT min and CT max) which track environmental temperatures. We test the thermal adaptation hypothesis at two biological levels of organization, the community and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 60 publications
6
44
2
Order By: Relevance
“…Explained deviance for patterns of relative abundance was, however, generally low across both sets of data. Our findings contrast with those for other insects where critical limits are related to geographic range (García‐Robledo et al., 2016; Sheldon & Tewksbury, 2014), but build on a growing understanding of the complexity of the relationship between critical limits and abundance and occupancy of ants (Bujan, Roeder, de Beurs, et al., 2020; Guo et al., 2020), which may also apply to ectotherms more broadly. Previous work has shown that in ants the relationship between critical limits and geographic range varies between local and global scales (Diamond & Chick, 2018; Nowrouzi et al., 2018).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Explained deviance for patterns of relative abundance was, however, generally low across both sets of data. Our findings contrast with those for other insects where critical limits are related to geographic range (García‐Robledo et al., 2016; Sheldon & Tewksbury, 2014), but build on a growing understanding of the complexity of the relationship between critical limits and abundance and occupancy of ants (Bujan, Roeder, de Beurs, et al., 2020; Guo et al., 2020), which may also apply to ectotherms more broadly. Previous work has shown that in ants the relationship between critical limits and geographic range varies between local and global scales (Diamond & Chick, 2018; Nowrouzi et al., 2018).…”
Section: Discussioncontrasting
confidence: 87%
“…Previous work has shown that in ants the relationship between critical limits and geographic range varies between local and global scales (Diamond & Chick, 2018; Nowrouzi et al., 2018). The relationship between environmental temperature and interspecific variation in occupancy and abundance has also been shown to depend on how likely environmental temperatures are to approach critical limits of a given species, either at the upper or lower ends (Bishop et al., 2017; Bujan, Roeder, de Beurs, et al., 2020; Diamond, Nichols, et al., 2012; Stuble, Pelini, et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical thermal limits (CTs) are temperatures at which animals lose muscle control (Lutterschmidt & Hutchison, 1997). To measure CTs, we used chilling/heating dry bath (Torrey Pines Scientific EchoTherm™ IC50; advertised accuracy ±0.2°C) and a standardized protocol for recording ant thermal limits (Bujan, Roeder, Beurs, et al., 2020). In this dynamic protocol, five workers per colony are individually tested.…”
Section: Methodsmentioning
confidence: 99%
“…Ectotherm heat tolerance exhibited strong phylogenetic conservatism in most studies, including ants (Diamond & Chick, 2018; Bujan et al , 2020), fruit flies (Kellermann et al ,2012a), or lizards (Grigg & Buckley, 2013). In contrast, other studies retrieved no evidence for a relationship between phylogeny and thermal tolerance (Bishop et al , 2017; Nowakowski et al , 2018).…”
Section: Discussionmentioning
confidence: 99%